Balanced branched‐chain amino acids modulate meat quality by adjusting muscle fiber type conversion and intramuscular fat deposition in finishing pigs. (5th January 2022) - Zhang, Lingyu; Li, Fengna; Guo, Qiuping; Duan, Yehui; Wang, Wenlong; Yang, Yuhuan; Yin, Yunju; Gong, Saiming; Han, Mengmeng; Yin, Yulong
Abstract: BACKGROUND: Pork is an important food for humans and improving the quality of pork is closely related to human health. This study was designed to investigate the effects of balanced branched‐chain amino acid (BCAA)‐supplemented protein‐restricted diets on meat quality, muscle fiber types, and intramuscular fat (IMF) in finishing pigs. RESULTS: The results showed that, compared with the normal protein diet (160 g kg −1 crude protein), the reduced‐protein diet (120 g kg −1 crude protein) supplemented with BCAAs to the ratio of 2:1:2 not only had higher average daily gain ( P  < 0.05) and carcass weight ( P  < 0.05) but also improved meat tenderness and juiciness by decreasing shear force ( P  < 0.05) and increasing water‐holding capacity ( P  < 0.05). In particular, this treatment showed higher ( P  < 0.05) levels of phospho‐acetyl‐CoA carboxylase (P‐ACC) and peroxisome proliferation‐activated receptor‐ γ (PPAR γ ), and lower ( P  < 0.05) levels of P‐adenosine 5'‐monophosphate (AMP)‐activated protein kinase (P‐AMPK), increasing the composition of IMF and MyHC I ( P  < 0.05) in the longissimus dorsi muscle (LDM). In terms of health, this group increased eicosapentaenoic acid (EPA) ( P  < 0.01) and desirable hypocholesterolemic fatty acids (DHFA) ( P  < 0.05), and decreased atherogenicity (AI) ( P  < 0.01) and hypercholesterolemic saturated fatty acids (HSFA) ( P  < 0.05). CONCLUSION: Our findings suggest a novel role for a balanced BCAA‐supplemented restricted protein (RP) diet in the epigenetic regulation of more tender and healthier pork by increasing IMF deposition and fiber type conversion, providing a cross‐regulatory molecular basis for revealing the nutritional regulation network of meat quality. © 2021 Society of Chemical Industry.